Improvement of microwave absorption properties via ceramic method and mechanical alloying processing of Ti-Co-Mn-Ni substituted barium ferrite - Chen, Hongxu (2024)
Many attempts have been made to identify nanomaterials with high reflection loss to improve electromagnetic microwave absorption. In this study, barium hexagonal nanocomposites (BaFe12O19) and substituted barium hexagonal ferrite composites BaTiCo0.5MnxNi0.5-xFe10O19 (x = 0.25, 0.3, 0.35, 0.4) were synthesized using high energy ball milling to investigate their magnetic and electromagnetic microwave adsorption properties. The goal is to address the challenge of creating homogeneous, fine-grained materials for high-GHz band applications, where electromagnetic interference remains a problem. Initially, the samples underwent processing optimization by several stages: mixing by mortar (M), calcination (C), sintering (S) and high energy ball milling (HEBM) (H) to determine the best method to obtain highly crystalline nanoparticles for Microwave Absorber (MA) materials. The calcination-sintering-HEBM (CSH) method proved to be the most effective and was used to prepare the MA composite. The raw powder underwent conventional milling for 5 hours, calcination at 1000 oC for 5 hours, sintering at 1300 oC for 5 hours, and then mechanical alloying for 5 hours. The samples were then investigated their structural, microstructural, elemental, magnetic, and microwave properties using an X-ray diffraction (XRD), a field emission scanning electron microscopy (FESEM), an energy dispersive X-ray analysis (EDX) a vibrating sample magnetometer (VSM), and a vector network analyzer (VNA). XRD data revealed that all the samples are crystalline ferrite with a hexagonal crystal structure. The XRD spectra showed that the peaks of the milled samples are broader than those of the un-milled samples, with the smallest particle size being 79.09 nm, as indicated by FESEM micrographs. VSM results exhibited that saturation magnetization (Ms) decreases with milling time and Mn content. The BaTiCo0.5Mn0.4Ni0.1Fe10O19 sample with the substitution value of x =0.4 had the lowest reflection loss (RL) of −40.37 dB at 13.7 GHz with at a thickness of 2 mm through a CSH synthesis. Thus, BaTiCo0.5Mn0.4Ni0.1Fe10O19 demonstrated excellent reflection loss and higher absorption of incident electromagnetic radiation, addressing the urgent problem of electromagnetic pollution.